Strategi Pendidikan Agama Hindu Berbasis Sad Dharma - Ida Ayu Nindia Brahmani Putri (Jayapangus Press, 2022)
The teachings of Sad Dharma become an important basis that can be used by educators in creating learning strategies that are able to direct students to apply the theories of religious education that they get. The values ​​of Sad Dharma's teachings are also very relevant to be applied at the level of education, both from Kindergarten (TK) and even college. The implementation of the Sad Dharma-based strategy is also part of the preservation of Balinese Hindu culture such as the dharma gita and dharam discourse which are rarely touched by the younger generation. What Sad Dharma are 6 dharma goals that must be carried out by Hindus indirectly through the implementation of Sad Dharma-based Hindu Religious Education strategies, educators are able to deliver their students to achieve these goals. The purpose of this study was to find out about the Sad Dharma-based Hindu education strategy. The research method is qualitative using secondary data sources, data collection techniques in this study use study documentation plus library techniques and when the data has been obtained and compiled in the form of scientific work, the author will perform data analysis. Overall, this sad dharma-based Hindu education strategy can provide maximum results in the quality of student education because its implementation is not only found in theory but also in action in implementing its teachings in line with the concept of learning that is currently being promoted by the government.